Kajian Aspek Biologi Stegobium Paniceum (Coleoptera: Anobimae) = Study On The Biological Aspects Of Stegobium Paniceum (Coleoptera: Anobiidae) - Perpustakaan UGM, i-lib ([Yogyakarta] : Perpustakaan UGM, 1998)
The biological aspects of Stegobium paniceum (L.)(Coleoptera: Anobiidae) was studied by culturing the insect on coriander seeds at the Laboratory of Research Center for Biological Control (RCBC), Gadjah Mada University, under room temperature of 26.5510.72°C - 30.66±0.40°C and 57.38±5.53% relative humidity. The results showed that egg, larval and pupal stages of S. paniceum were 9.15±1.37